2020
DOI: 10.1126/science.aax5758
|View full text |Cite
|
Sign up to set email alerts
|

Strengthening of the Kuroshio current by intensifying tropical cyclones

Abstract: A positive feedback mechanism between tropical cyclones (TCs) and climate warming can be seen by examining TC-induced energy and potential vorticity (PV) changes of oceanic geostrophic eddies. We found that substantial dissipation of eddies, with a strong bias toward dissipation of anticyclonic eddies, is directly linked to TC activity. East of Taiwan, where TCs show a remarkable intensifying trend in recent decades, the ocean exhibits a corresponding upward trend of positive PV anomalies. Carried westward by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
38
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(42 citation statements)
references
References 53 publications
1
38
3
Order By: Relevance
“…This vigorous poleward western boundary current creates a complex ocean current system when it flows over steep topography northeast of Taiwan where canyons often cut through the continental slope (e.g., X. Guo et al., 2006, 2003; Hsueh et al., 1993, 1997, 1992; Tang et al., 2000; Yang et al., 2012, 2018, 2011). Moreover, this current system becomes even more complex due to the energetic interactions between the Kuroshio and westward propagating mesoscale eddies that originate from the tropical North Pacific (e.g., Vélez‐Belchí et al., 2013; Y. Zhang et al., 2020).…”
Section: Introductionmentioning
confidence: 99%
“…This vigorous poleward western boundary current creates a complex ocean current system when it flows over steep topography northeast of Taiwan where canyons often cut through the continental slope (e.g., X. Guo et al., 2006, 2003; Hsueh et al., 1993, 1997, 1992; Tang et al., 2000; Yang et al., 2012, 2018, 2011). Moreover, this current system becomes even more complex due to the energetic interactions between the Kuroshio and westward propagating mesoscale eddies that originate from the tropical North Pacific (e.g., Vélez‐Belchí et al., 2013; Y. Zhang et al., 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Compared with the scheme based on wind speed, schemes based on wave state describe the physical state of the sea surface more directly and are often used in the atmosphere-ocean-wave coupling model, in which the wave state is provided by the ocean model or the wave model. e heat transported from ocean to atmosphere is the main energy source for typhoon [30,31]. Due to the difficulties in measuring heat flux directly, the mechanism of airsea heat transfer is relatively dubious.…”
Section: Introductionmentioning
confidence: 99%
“…Under the globally warming atmosphere and ocean, sequential typhoons have increasingly significant effects on the ecological environments of oceans and coastal residents, so the interaction between sequential typhoons and oceans has attracted an increasing amount of attention [25][26][27]. However, their studies did not distinguish between different mesoscale eddy features: a dynamic feature that is ubiquitous in the ocean [33] and important for the typhoon-ocean interaction [67]. Yang et al [25] and Wu et al [26] mainly showed the responses in the CEs, and the research results of Zhang et al [27] were mainly based on observations of Station 2 located in an AE.…”
Section: Discussionmentioning
confidence: 99%
“…The sequential typhoons studied in the past almost occurred in the SCS, and the NWP is the region with a high frequency of typhoon genesis [31], accounting for more than twenty typhoons every year [32]. In addition, the NWP is also one of the most active mesoscale eddy regions, in which the Kuroshio has rich ocean dynamic characteristics, such as ubiquitous mesoscale eddy movement [33]. Due to the large-scale flow, typhoons generated in the NWP tend to move northwestwards, and the landfalling typhoons will cross the Kuroshio.…”
Section: Introductionmentioning
confidence: 99%